Evaluation on the tribological properties of double fractionated palm olein at different load using pin-on-disk machine - Noorawzi, Nuraliza (2015)
The use of vegetable oil-based lubricant as a lubricant in various applications has increased and it is eyed by the industry due to its superior tribological properties, besides possessing the potential to replace petroleum-based lubricants. Palm olein is one of alternative lubricants that could be suitable and attractive as a lubricant to be studied due to its advantages and large production in the country. Thus, in this study, the behavior of palm olein characteristics was investigated by using pin-on-disc experiment, in which a hemispherical pin was loaded against the rotating grooved disc. The experiments via sliding were performed with pin-on-disc tester using pure aluminum as the material for hemispherical pin and SKD11 for disc. The test was implemented by dropping continuous flow of palm olein as lubricating oil on sliding surface at different loads applied, which were 10N, 50N, and 100N. The wear rate of the pin and the friction coefficient were also investigated. Moreover, the surface roughness before and after the experiment was analyzed as well. All the results obtained were compared to hydraulic oil and engine oil-SAE 40. From the analysis, the friction coefficient acquired from lubricated with palm olein was the lowest for both conditions. The wear rate obtained for the three lubricants increased from 10N to 100N load for palm oil, but decreased for hydraulic and engine oil-SAE 40. Meanwhile, the wear rate obtained for lubrication with hydraulic oil showed the lowest value compared to Engine oil-SAE 40 and double fractionated palm olein.